Effect of soaking, germination and drying on anti-nutrients and minerals present in horsegram - Athawale, Gauri; Devkatte, Anupama; Akbari, Sanjay; Pawar, Vasant; Raichurkar, Shweta (Journal of Postharvest Technology, 2022)
Horse gram (Macrotyloma uniflorum) is legume, which has a place with family Fabaceace. It is a potential grain legume having excellent wholesome quality and least expensive source of protein. It is rich in calcium and iron. Most extreme use of horse gram is missing because of the presence of anti nutritional factors like tannin and phytic acid which interferes with the bioavailability of nutrients present in horse gram. The anti-nutritional factors, mineral content of raw and germinated horse gram were evaluated after giving varied pretreatments of soaking, germination and drying. Treatment of 6hrs soaking, 72hrs germination and drying at 70˚C gave maximum decrease in the anti-nutritional factors i.e. tannin and phytic acid (24.77% and 39.66%), respectively. At the same time mineral content was reduced i.e. calcium and iron content (31.68% and 20.68%), respectively. It can be observed that all this pretreatment played vital role in reduction in both anti-nutritional factors and mineral content.